2018
DOI: 10.1002/bio.3467
|View full text |Cite
|
Sign up to set email alerts
|

Detection of metronidazole in honey and metronidazole tablets using carbon dots‐based sensor via the inner filter effect

Abstract: In this work, carbon dots (CDs) with a high quantum yield (22.3%) were easily prepared by hydrothermal pyrolysis of acid fuchsin 6B and hydrogen peroxide at 180°C for 10 h. The resultant CDs possess a narrow size distribution in the range of 2.6 to 3.2 nm and emit blue fluorescence. Interestingly, the absorption band of metronidazole (MTZ) centered at 318 nm can complementary overlap with the excitation band of the as-prepared CDs centered at 320 nm, resulting in an inner filter effect (IFE) in high efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Figure c shows the optimum emission and excitation wavelengths are 414 and the 340 nm, respectively. For the CDs, the black line is the UV spectrum, and the transitions of π → π* (248 nm) and n → π* (300–500 nm) are confirmed . The red line and the green line are the excitation (340 nm) and emission (414 nm) spectra of the CDs, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Figure c shows the optimum emission and excitation wavelengths are 414 and the 340 nm, respectively. For the CDs, the black line is the UV spectrum, and the transitions of π → π* (248 nm) and n → π* (300–500 nm) are confirmed . The red line and the green line are the excitation (340 nm) and emission (414 nm) spectra of the CDs, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…Multimodal detection has been the one of research directions for many researchers. At first, people can only detect one substance by one mode, for example, metronidazole is detected by ET [17]. Later improvements were made, three kinds of metal ions are detected by changing the buffer solution [16], three kinds of medicines were analysed by switching different quenching manners [5] and triple-mode emissions were also studied [18].…”
Section: Discussionmentioning
confidence: 99%
“…As a non‐radiative dipole–dipole energy transfer process, CRET can take place from a chemiluminescent donor to a fluorophore acceptor in close range (< 10 nm), and the prerequisite is that there must be an overlapping between CL emission spectrum of the donor and the absorption spectrum of the fluorescent acceptor. In addition, CDs may also have an intriguing potential for catalysis, taking advantage of the extremely large surface area, good biocompatibility, and high adsorption capacity . In general, CDs can identify themselves as luminescent species, energy acceptor, catalysts or others in the CL reactions.…”
Section: Cds‐assisted CL Systemsmentioning
confidence: 99%
“…More recently, in addition to the valuable efforts on mechanistic elucidation, it was observed that the PL emission of CDs could be quenched efficiently by 2,4‐dinitrotoluene (the known electron acceptors) or the photoreduction of Ag + to Ag in solution, verifying the electronic properties of CDs as electron donors and acceptors . These properties could make CDs perhaps both participation in chemiluminescence (CL) or electrochemical luminescence, and even wide potentials in optronics, catalysis and sensors as a futuristic luminescence material …”
Section: Introductionmentioning
confidence: 95%